ChemInform Abstract: Sunlight‐Driven Trifluoromethylation of Olefinic Substrates by Photoredox Catalysis: A Green Organic Process. Issue 41 (October 2015) - Akita, Munetaka; Koike, Takashi
Abstract Review: 101 refs.